A comparison of people with posttraumatic stress who received and those have neither sougth nor received specialized treatment following traumatic war related experience - Priebe, Stefan; Ljubotina, Damir; Pantić, Zdenka Frančišković, Tanja; Kučukalić, Abdulah Janković Gavrilović, Jelena; Schuetzwohl, Matthias (2007)
One of the main aims of the STOP study was to identify in what way patients with posttraumatic stress who have received professional help in specialized treatment centers differ from people suffering from posttraumatic stress who have neither sought nor received specialized treatment. Total sample consists of 526 patients who were treated in 4 specialized centers and 600 traumatized persons in the community who have neither sought nor received specialized treatment. The study also assessed whether the characteristics (traumatic experience, level of posttraumatic symptoms, coping strategies) of refugee non-treatment seekers resettled in Germany and the UK differ from those who stayed in the Balkans. When the overall degree of traumatic experience is controlled for, non-treatment seekers show higher scores on psychopathological dimensions, but report similar level of PTSD symptoms. At the same time, they report more social acknowledgement, better subjecive quality of life and more frequent use of adaptive coping strategies than treatment seekers. Preliminary results show that refugees resettled in Western Europe report a higher level of PTSD symptoms and general psychopathology than refugees and civilians in the post-war area. Our analyses indicate that correlation between level of traumatization and symptomatology is moderated by factors of posttraumatic environment
Projekt MZOS
ENG